Reduction in Pain and Pain Intensity with Nonpharmacological Treatment in Severely Obese Patients: A Randomized Clinical Trial - Carolina Rodrigues Mendonça (MDPI AG, 2021)
The objective of this study was to analyze the effectiveness of two nonpharmacological interventions—traditional Brazilian diet (DieTBra), and extra-virgin olive oil (EVOO)—in terms of the reduction in pain and pain intensity in individuals with severe obesity. We conducted a 12-week parallel randomized clinical trial with 149 individuals (body mass index (BMI) ≥ 35 kg/m2) who were randomized into three groups: supplementation with EVOO (n = 50), DieTBra (n = 49), and EVOO + DieTBra (n = 50). Of the total, 133 individuals with a mean BMI of 46.04 kg/m2 completed the study. By the end of the follow-up, there was a reduction in severe pain in the EVOO + DieTBra group (p = 0.003). There was a significant reduction in severe pain in the EVOO + DieTBra group (−22.7%); pain in the wrist and hand (−14.1%), upper back (−26.9%), and knees (−18.4%) in the DieTBra group; and reduction in hip pain (−11.1%) with EVOO consumption. We conclude that EVOO and DieTBra, either alone or in combination, are effective interventions to reduce pain intensity and pain in different regions in individuals with severe obesity, and have great potential for clinical application.